Social Support on the Adherence to Treatment of Tuberculosis in Cilacap, Indonesia - Lina Puspitasari; Bhisma Murti; Argyo Demartoto (Masters Program in Public Health, 2016)
Background: Country Indonesia liquid high-burden countries in the case of Tuberculosis resistant adenocarcinoma. One of the causes of MDR-TB was OAT drink irregularly. Many of the changes that occur in people with tuberculosis physical, psychological and social influence on irregularity OAT drink. The purpose of this research is to know the contribution of the social support against tuberculosis treatment regularity in Cilacap Regency.Subject and Method: This was a quantitative study with observational analytic design, carried out in twelve clinics and hospitals, inCilacap. A total of 128 samples were consisted of 42 groups and control group 86. The dependent variables was the regularity of the medication, and the independent variable were the intention, attitude, distance, self-efficacy, social support, education and knowledge. The Data collected using the questionnaire and medical record data and analyzed usingpath analysis.Results: There is a direct relationship between education with knowledge, education and knowledge, as well as attitudes toward intentions with the regularity of medical treatment. There is an indirect relationship between posture, distance, social support and self-efficacy with the OAT drink regularity through intention. A positive relationship between education with knowledge (b = 0.17; 95%CI = 0.02 to 0.13; p = 0.023). A positive relationship between education with attitude (b = 1.23; 95% CI = 0.29 to 2.16; p = 0.01). Positive relationship knowledge with attitude (b = 0.56; 95% CI =-1.47 to 0.35; p = 0.228). The relationship of positive attitude with the intention (b = 0.99; CI 95% = 0.05 to 1.94; p = 0.039). Negative relationship of distance with the intention (b =-0.59; 95% CI =-1.49 to 0.31; p = 0.202). Positive relationships support social (social support) and intention (b = 0.5; 95% CI =-0.22 to 1.89; p = 0123). A positive relationship with self-efficacy of intention (b = 1.04;95% CI =-0.16 to 2.26; p = 0.089). A positive relationship with the intention to ordertreatment of TB (b = 2.1; CI 95% = 1.24 to 2.97; p = 0.001).Conclusion: Education, knowledge, attitude, social support self-efficacy related to improve the regularity of treatment of TB through the intention to treat.Keywords:Attitude, Distance, Social Support, Self-Efficacy, Consistency of Treatment of TBCorrespondence: Lina Puspitasari. Midwifery Academic Graha Mandiri Cilacap. Email: Lina_Puspitasari@yahoo.co.idJournal of Epidemiology and Public Health, 2016, 1(1): 58-65https://doi.org/10.26911/jepublichealth.2016.01.01.07